Patients' use of physical therapy for lower back pain: A qualitative study. (December 2021) - Sharpe, Jason A.; Thackeray, Anne; Fritz, Julie M.; Martin, Brook I.; Magel, John; Vanneman, Megan E.
Abstract: Objective: The purpose of this study was to identify factors that influence a patient's decision to use physical therapy (PT) services for a low back pain (LBP) complaint. Methods: Semi-structured qualitative phone interviews were conducted with patients who were offered an early outpatient PT visit secondary to patients' primary appointment for LBP with a non-operative sports medicine specialist physician. Interviews were recorded, transcribed, and analyzed to identify themes using an iterative process. Results: Forty participants were interviewed; 20 accepted early PT services, and 20 did not. Patients' decisions were influenced by perceived provider training, costs, doctor recommendations, wait times, symptoms, and a desire for a diagnosis. Patients preferred the care of non-operative sports medicine doctors over physical therapists for LBP due to their beliefs that favored doctors' diagnosis and management of LBP. Patients perceived exercise as an effective treatment for back pain. Physical therapists were viewed as an adjunct service, despite positive comments about PT and the belief that exercise is one of the most effective treatments for LBP. Conclusion: Barriers including costs, patient preferences, and knowledge about physical therapists limited patients' use of PT. Value-based care strategies aimed at improving the management of LBP increasingly promote the early use of PT. For these strategies to be effective, it is critical that patient perceptions and the influence of barriers on PT use are further understood. This study highlights the need to promote confidence in physical therapists' expertise in the management and diagnosis of lower back pain. Highlights: Patient knowledge limited PT use but not doctor use. Patients believed exercise is an effective treatment for LBP. Sport medicine doctors were preferred over physical therapists for LBP. Challenges navigating the health care system reduced patients' access PT care. Patient decisions are influenced by a large variety of factors.